FREQUENCY OF HEART RATE BALI FEMALE CATTLE IN THE SECOND TRIMESTER OF PREGNANCY - L Rona, Tiara; Suartha, I Nyoman; Budiasa, I Made Kota (Buletin Veteriner Udayana, 2016)
Bali cattle is one of national cattle germplasm from Bali that needs to be conserved especially the female cattle. Currently, there have not been unreported research about heart rate of bali cattle’s and still be guided by others breed cattle’s. This research aim to determine inventory of heart rate bali female cattle in the second trimester of pregnancy. Cattle’s are examinating came from the bali cattle’s breeding centre in Sobangan village Mengwi district Badung regency amount to fiveteen cattle’s. Analysis data used descriptive test and then T test. The result research shown mean of the old pregnancy from 4 month, 5 month and 6 month heart rate of bali female cattle’s in the second trimester of pregnancy is 67,40±8,41/minutes, 75,93±8,62/minutes and 76,06±11,40/minutes. The conclusion for this research is more old pregnancy of bali cattle then frequency of heart rate also increase.
Keywords: sapi bali; plasma nutfah; frekuensi detak jantung; bali cattle; germplasm; frequency of heart rate